Non-aqueous electrolyte battery

A lithium-aluminum alloy layer with a carbon coating on the negative electrode addresses the performance imbalance in non-hydrolyzed liquid batteries, enhancing high-temperature storage and low-temperature load characteristics by stabilizing the battery's discharge capacity.

JP7623940B2Active Publication Date: 2025-01-29MAXELL LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021526061
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-10
Filing Date
2020-06-05
Publication Date
2025-01-29
Estimated Expiration
2040-06-05

AI Technical Summary

Technical Problem

Non-hydrolyzed liquid batteries face challenges in maintaining balanced performance characteristics at both high and low temperatures, particularly due to reactions between the electrolyte and electrode at high temperatures leading to swelling and decreased discharge characteristics.

Method used

The battery incorporates a lithium-aluminum alloy layer on the negative electrode surface with a carbon layer formed on top, enhancing the negative electrode by forming a laminated body with a lithium layer and an aluminum layer, which is then reacted to create a lithium-aluminum alloy layer.

Benefits of technology

This configuration improves high-temperature storage characteristics and low-temperature load characteristics by suppressing the decrease in battery performance during high-temperature storage and maintaining discharge capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623940000002
    Figure 0007623940000002
  • Figure 0007623940000003
    Figure 0007623940000003
  • Figure 0007623940000001
    Figure 0007623940000001
Patent Text Reader

Abstract

Provided are: a non-aqueous electrolyte battery that has excellent high-temperature storage characteristics and low-temperature load characteristics; and a production method for the non-aqueous electrolyte battery. This non-aqueous electrolyte battery is characterized by including a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte. The negative electrode has: a lithium layer that has a lithium-aluminum alloy layer formed on the surface thereof; and a carbon layer that is on the lithium-aluminum alloy layer. The non-aqueous electrolyte battery can be produced by means of a method that includes a step in which a lithium-aluminum alloy layer is formed by reacting a lithium layer and an aluminum layer of a negative electrode laminate that has been formed by forming a carbon layer on the surface of an aluminum layer of a laminate that has an aluminum layer on the surface of a lithium layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte battery having excellent high-temperature storage characteristics and low-temperature load characteristics, and a method for manufacturing the same. [Background technology]

[0002] At present, non-aqueous electrolyte batteries, such as lithium primary batteries and lithium ion secondary batteries, having a non-aqueous electrolyte, are used in a variety of fields, including as power sources for portable devices as well as for applications exposed to high temperatures and large vibrations, such as power sources for pressure sensors inside tires. In response to the expansion of their applications, attempts are being made to improve various characteristics.

[0003] However, when a battery is stored at high temperatures, a reaction occurs between the electrolyte and the electrodes, resulting in problems such as battery swelling. Therefore, in applications where the battery is used in a high-temperature environment, measures are required to suppress the reaction between the electrolyte and the electrodes.

[0004] In response to this, sulfur-based compounds such as propane sultone are known as additives that form a coating on the surface of the positive or negative electrode to suppress reaction with the electrolyte and prevent the battery from swelling during high-temperature storage (Patent Document 1).

[0005] Patent Document 2 discloses that by using a nonaqueous electrolyte containing lithium bis(oxalato)borate [LiB(C2O4)2] and LiBF4 in a molar ratio of 2:8 to 5:5, it is possible to form a battery that has excellent characteristics both at low and high temperatures by preventing an increase in internal resistance caused by moisture liberated from the positive electrode active material into the electrolyte at high temperatures and an increase in internal pressure caused by decomposition of the electrolyte.

[0006] However, when additives such as propane sultone or lithium bis(oxalato)borate are added to the electrolyte solution so as to produce a sufficient effect, a coating formed on the surface of the negative electrode, for example, inhibits the discharge reaction and increases the internal resistance of the battery, which can easily cause problems such as a decrease in discharge characteristics after high-temperature storage.

[0007] On the other hand, Patent Documents 3 and 4 propose forming a carbon-containing layer on the surface of the negative electrode as an alternative method to the above-mentioned additives. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2004-47413 A [Patent Document 2] JP 2006-269173 A [Patent Document 3] JP 2010-257828 A [Patent Document 4] JP 2011-091034 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, non-aqueous electrolyte batteries are now required to have battery characteristics that enable them to be used in a wide range of temperature environments, including not only high temperatures but also low temperatures. Further investigation is therefore required to achieve both high temperature storage characteristics and low temperature load characteristics.

[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a nonaqueous electrolyte battery having excellent high-temperature storage characteristics and low-temperature load characteristics, and a method for manufacturing the same. [Means for solving the problem]

[0011] The nonaqueous electrolyte battery of the present invention comprises a positive electrode, a negative electrode, a separator and a nonaqueous electrolyte, the negative electrode having a lithium layer on a surface of which a lithium-aluminum alloy layer is formed, and further having a carbon layer on the lithium-aluminum alloy layer.

[0012] The nonaqueous electrolyte battery of the present invention can be produced by a production method (a production method for the nonaqueous electrolyte battery of the present invention) including the steps of laminating an aluminum layer on a surface of a lithium layer, further forming a carbon layer on the surface of the aluminum layer, and reacting the lithium layer with the aluminum layer to form a lithium-aluminum alloy layer on the surface of the lithium layer. Effect of the Invention

[0013] According to the present invention, it is possible to provide a nonaqueous electrolyte battery having excellent high-temperature storage characteristics and low-temperature load characteristics, and a method for producing the same. [Brief description of the drawings]

[0014] [Figure 1] 1 is a longitudinal sectional view that illustrates a schematic diagram of an example of a nonaqueous electrolyte battery of the present invention. [Diagram 2] 4 is a graph showing the results of measuring the discharge voltage in the nonaqueous electrolyte battery of the example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The nonaqueous electrolyte battery of the present invention contains a negative electrode having a lithium layer with a lithium-aluminum alloy layer formed on the surface thereof and a carbon layer on the lithium-aluminum alloy layer. Although the reason is unclear, the use of the negative electrode suppresses the deterioration of battery characteristics during high-temperature storage, and makes it possible to improve the load characteristics at low temperatures (for example, the load characteristics at low temperatures of about -40°C) of the nonaqueous electrolyte battery after high-temperature storage.

[0016] The lithium-aluminum alloy layer of the negative electrode can be formed, for example, by providing an aluminum layer made of aluminum foil or aluminum alloy foil on the surface of a lithium layer made of lithium foil or lithium alloy foil to form a laminate, and further forming a carbon layer on the surface of the aluminum layer in the laminate (the surface opposite to the lithium layer), thereby contacting the negative electrode laminate with a nonaqueous electrolyte to cause a reaction between the lithium layer and the aluminum layer.

[0017] When the negative electrode laminate is brought into contact with a non-aqueous electrolyte to form a lithium-aluminum alloy layer, this may be carried out before the battery is assembled. In this case, the negative electrode obtained by changing the aluminum layer of the negative electrode laminate into a lithium-aluminum alloy layer is used for the assembly of a non-aqueous electrolyte battery. On the other hand, a battery may be assembled using the negative electrode laminate instead of a negative electrode, and during the assembly, the negative electrode laminate may be brought into contact with a non-aqueous electrolyte to form a lithium-aluminum alloy layer in the same manner as above to obtain a negative electrode. In this case, the manufacturing process of the negative electrode before the battery is assembled can be simplified, which is preferable in that the productivity of the battery can be further improved.

[0018] Examples of the lithium foil or lithium alloy foil for forming the lithium layer include a foil (lithium foil) made of Li (and unavoidable impurities), and a foil (lithium alloy foil) made of a Li alloy containing alloy components such as Fe, Ni, Co, Mn, Cr, V, Ti, Zr, Nb, Mo, etc. in a total amount of 40 mass % or less, preferably 10 mass % or less, and more preferably 5 mass % or less, with the remainder being Li and unavoidable impurities.

[0019] The thickness of the lithium foil or lithium alloy foil for forming the lithium layer is preferably 0.1 to 1.5 mm.

[0020] Examples of the aluminum foil or aluminum alloy foil for constituting the aluminum layer include a foil (aluminum foil) made of Al (and unavoidable impurities), and a foil (aluminum alloy foil) made of an Al alloy containing alloy components such as Fe, Ni, Co, Mn, Cr, V, Ti, Zr, Nb, Mo, etc., with the balance being Al and unavoidable impurities (the content of the alloy components is, for example, 50 mass % or less in total, preferably 10 mass % or less, and more preferably 5 mass % or less).

[0021] The thickness of the aluminum foil or aluminum alloy foil for constituting the aluminum layer is preferably 1 μm or more, more preferably 3 μm or more, and particularly preferably 5 μm or more, in order to clarify the effects of the present invention due to the formation of the lithium-aluminum alloy layer.

[0022] On the other hand, if the ratio of the lithium-aluminum alloy layer to the lithium layer is too high, the capacity of the negative electrode will decrease. Also, when the aluminum layer is alloyed with lithium, the volume expansion causes cracks in the aluminum layer (aluminum alloy layer), but if the thickness of the aluminum layer is thick, the cracks will occur deep inside the negative electrode, and there is a risk that a part of the aluminum alloy layer will fall off when subjected to large vibrations. Therefore, in order to keep the thickness of the lithium-aluminum alloy layer to a certain level or less, the thickness of the aluminum foil or aluminum alloy foil is preferably 20 μm or less, more preferably 15 μm or less.

[0023] The aluminum alloy layer does not have to be formed on the entire surface of the lithium layer, and may be formed on a part of the surface of the lithium layer. However, since the effect of the present invention is more easily achieved as the proportion of the area on which the aluminum alloy layer is formed on the surface of the lithium layer increases, the proportion of the area on which the aluminum alloy layer is formed on the surface of the lithium layer is preferably 40% or more, more preferably 70% or more, and most preferably 100%, i.e., the aluminum alloy layer is formed on the entire surface of the lithium layer.

[0024] The aluminum layer can be formed on one or both sides of the lithium layer depending on the form of the battery. For example, in a battery in which a positive electrode is disposed on both sides of a lithium layer of a negative electrode, an aluminum layer can be provided on both sides of the lithium layer to form a lithium-aluminum alloy layer.

[0025] A laminate having a lithium layer and an aluminum layer can be formed by laminating lithium foil or lithium alloy foil for constituting the lithium layer and aluminum foil or aluminum alloy foil for constituting the aluminum layer, and bonding them by pressure or the like.

[0026] The carbon layer of the negative electrode may be composed of only carbon (carbon particles), but may also contain a binder together with carbon.

[0027] Examples of carbon constituting the carbon layer include carbon black such as furnace black, channel black, acetylene black, and thermal black; graphite such as natural graphite (e.g., flake graphite) and artificial graphite; and the like. Only one of these may be used, or two or more of them may be used in combination.

[0028] Examples of binders that can be used in the carbon layer include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyvinylpyrrolidone, etc. In particular, compounds having a five-membered ring lactam structure such as polyvinylpyrrolidone are preferably used because they can disperse fine carbon materials such as carbon black well when dissolved in a solvent.

[0029] The content of the binder in the carbon layer is preferably 2 mass % or less, more preferably 1 mass % or less, and particularly preferably 0.5 mass % or less.

[0030] The basis weight of the carbon layer in the negative electrode is set to 0.15 mg / cm from the viewpoint of satisfactorily ensuring the above-mentioned effects due to the formation of the carbon layer. 2 It is preferable that the concentration is 0.3 mg / cm or more. 2 More preferably, it is 0.5 mg / cm or more. 2 It is particularly preferable that the carbon layer is thicker than 1.5 mg / cm2. However, even if the carbon layer is thicker, the effect is saturated, and the negative electrode as a whole becomes thicker, which may cause a decrease in the capacity of the battery, for example, by reducing the amount of positive electrode active material that can be introduced into the battery. Therefore, from the viewpoint of increasing the capacity of the battery, for example, the basis weight of the carbon layer in the negative electrode is set to 1.5 mg / cm2. 2 Preferably, it is 1.0 mg / cm or less. 2 It is more preferable that:

[0031] The carbon layer does not have to be formed on the entire surface of the aluminum alloy layer, and may be formed on a part of the surface of the aluminum alloy layer. That is, a part of the aluminum alloy layer may be exposed on the surface of the negative electrode without being covered with a carbon layer. For example, when the lithium-aluminum alloy layer is formed, its surface may become uneven, and the convex parts may be exposed on the surface of the negative electrode. Also, there may be a part of the surface of the lithium layer where the aluminum alloy layer is not formed and the carbon layer is directly formed.

[0032] However, since the effect of the present invention is more easily achieved as the proportion of the area of ​​the portion on the lithium layer where the aluminum alloy layer and the carbon layer are formed increases, the proportion of the area of ​​the surface of the aluminum alloy layer where the carbon layer is formed is preferably 40% or more, more preferably 70% or more, and particularly preferably 100%, i.e., the carbon layer is formed over the entire surface of the aluminum alloy layer.

[0033] Furthermore, it is most preferable that an aluminum alloy layer is formed on the entire surface of the lithium layer, and a carbon layer is formed on the entire surface of the aluminum alloy layer.

[0034] The carbon layer can be formed, for example, by a method in which a composition for forming a carbon layer (a liquid composition such as a paste or a slurry) prepared by dispersing carbon and, further, a binder added as necessary, in an organic solvent (the binder may be dissolved), is applied to the surface of the aluminum layer in a laminate having a lithium layer and an aluminum layer, and then dried.

[0035] As the organic solvent used in the carbon layer forming composition, a solvent used in the non-aqueous electrolyte of the battery is preferably used. Specific examples of such a solvent include cyclic carbonates such as ethylene carbonate, propylene carbonate (PC), butylene carbonate, and vinylene carbonate; chain carbonates such as dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate; ethers such as 1,2-dimethoxyethane (DME), diglyme (diethylene glycol dimethyl ether), triglyme (triethylene glycol dimethyl ether), tetraglyme (tetraethylene glycol dimethyl ether), methoxyethoxyethane, 1,2-diethoxyethane, and tetrahydrofuran; cyclic esters such as γ-butyrolactone; and nitriles. One or more of these solvents can be used, but carbonates such as propylene carbonate react with lithium to form lithium carbonate, which may reduce the reactivity of the negative electrode surface. Therefore, from the viewpoint of making it easier to exhibit the effects of the present invention, it is preferable to use a solvent other than carbonates, and it is more preferable to use ethers, and it is even more preferable to use DME.

[0036] In addition, as the organic solvent used in the carbon layer forming composition, a solvent used in forming a paint such as a slurry containing a positive electrode active material can be used, and when a fine carbon material such as carbon black is used, a compound having a five-membered ring lactam structure such as 2-pyrrolidone or N-methyl-2-pyrrolidone (NMP) can be preferably used because it can disperse the carbon material well. The compound having a five-membered ring lactam structure can also be used by mixing with the solvent used in the nonaqueous electrolyte.

[0037] The negative electrode can be composed of only a lithium layer, a lithium-aluminum alloy layer and a carbon layer, but may further include a current collector as necessary.

[0038] Examples of the negative electrode current collector include those made of copper, nickel, iron, and stainless steel, and examples of the form of the current collector include plain woven wire mesh, expanded metal, lath mesh, punched metal, metal foam, and foil (plate). The thickness of the current collector is preferably, for example, 5 to 100 μm. It is also desirable to apply a paste-like conductive material such as carbon paste or silver paste to the surface of such a current collector.

[0039] For the positive electrode of the nonaqueous electrolyte battery, for example, a compact obtained by molding a mixture (positive electrode mixture) containing a positive electrode active material, a conductive assistant, a binder, etc. into a pellet shape, or a structure having a layer (positive electrode mixture layer) made of the positive electrode mixture on one or both sides of a current collector can be used.

[0040] Examples of the positive electrode active material include manganese dioxide, lithium-containing manganese oxides (e.g., LiMn3O6, and composite oxides having the same crystal structure as manganese dioxide (e.g., β-type, γ-type, or a mixed structure of β-type and γ-type) and a Li content of 3.5% by mass or less, preferably 2% by mass or less, more preferably 1.5% by mass or less, and particularly preferably 1% by mass or less), Li a Ti 5 / 3 Examples of the oxides include lithium-containing composite oxides such as O4 (4 / 3≦a<7 / 3); vanadium oxide; niobium oxide; titanium oxide; sulfides such as iron disulfide; and graphite fluoride.

[0041] Examples of the conductive assistant for the positive electrode mixture include flake graphite, acetylene black, ketjen black, and carbon black. Only one of these may be used, or two or more of them may be used in combination.

[0042] Furthermore, examples of the binder for the positive electrode mixture include fluororesins such as PVDF, PTFE, and polymers of propylene hexafluoride. Only one of these may be used, or two or more of them may be used in combination.

[0043] In the case of a positive electrode molded body of a positive electrode mixture, the positive electrode can be manufactured, for example, by pressurizing a positive electrode mixture prepared by mixing a positive electrode active material, a conductive assistant, a binder, and the like into a predetermined shape.

[0044] Furthermore, in the case of a positive electrode having a positive electrode mixture layer and a current collector, for example, a positive electrode active material, a conductive assistant, a binder, and the like are dispersed in water or an organic solvent such as N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode mixture-containing composition (slurry, paste, and the like) (the binder may be dissolved in the solvent), which is then applied onto a current collector, dried, and, if necessary, subjected to a pressing process such as a calendaring process, thereby producing the positive electrode.

[0045] However, the positive electrode is not limited to those produced by the above-mentioned methods, and may be produced by other methods.

[0046] As for the composition of the positive electrode mixture for the positive electrode, the amount of the positive electrode active material is preferably 80 to 90 mass %, the content of the conductive assistant is preferably 1.5 to 10 mass %, and the content of the binder is preferably 0.3 to 10 mass %.

[0047] In the case of a positive electrode mixture molded body, the thickness is preferably 0.15 to 4 mm. On the other hand, in the case of a positive electrode having a positive electrode mixture layer and a current collector, the thickness of the positive electrode mixture layer (thickness per one side of the current collector) is preferably 30 to 300 μm.

[0048] When a current collector is used for the positive electrode, the current collector may be made of stainless steel such as SUS316, SUS430, or SUS444, and may be in the form of a plain woven wire mesh, an expanded metal, a lath mesh, a punched metal, a metal foam, or a foil (plate). The thickness of the current collector is preferably, for example, 0.05 to 0.2 mm. It is also desirable to apply a paste-like conductive material such as carbon paste or silver paste to the surface of such a current collector.

[0049] The nonaqueous electrolyte battery of the present invention is assembled using a laminate (laminated electrode body) in which the negative electrode and the positive electrode are laminated with a separator interposed therebetween, a wound body (wound electrode body) in which this laminate is spirally wound, and a flat wound body (flat wound electrode body) in which this wound body is molded so that its cross section is flat. The nonaqueous electrolyte battery of the present invention can also be assembled by using a positive electrode made of a molded body of a positive electrode mixture and the negative electrode, and housing them in a flat battery case with a separator interposed between them.

[0050] Alternatively, a battery may be assembled using the negative electrode laminate in place of the negative electrode, and the negative electrode may be formed during the assembly.

[0051] A nonwoven fabric or a microporous film is used for the separator, and as the material thereof, polyolefins such as polyethylene (PE), polypropylene (PP), and ethylene-propylene copolymers can be used. In addition, when heat resistance is required in relation to the use of the battery, fluororesins such as tetrafluoroethylene-perfluoroalkoxyethylene copolymers (PFA), polyphenylene sulfide (PPS), polyether ether ketone (PEEK), polybutylene terephthalate (PBT), polymethylpentene, polyamide, polyimide, aramid, cellulose, etc. can also be used. The material of the nonwoven fabric or microporous film may be one of the above-mentioned examples, or two or more of them. In addition, the nonwoven fabric or microporous film to be the separator may have a single-layer structure made of the above-mentioned materials, or may have a laminate structure in which multiple nonwoven fabrics or microporous films made of different materials are laminated.

[0052] From the viewpoint of suppressing a decrease in the energy density of the battery, the thickness of the separator may be, for example, 500 μm or less, preferably 450 μm or less, and more preferably 300 μm or less. However, if the separator is too thin, the function of preventing short circuits may be reduced, so that, when a nonwoven fabric is used, the thickness may be, for example, 30 μm or more, preferably 100 μm or more, and more preferably 150 μm or more. Furthermore, when a microporous membrane is used, the thickness is preferably 10 μm or more, and more preferably 15 μm or more.

[0053] The non-aqueous electrolyte of the non-aqueous electrolyte battery may be prepared by dissolving LiPF6, LiBF4, LiClO4, LiCF3SO3, etc., as an electrolyte in an organic solvent. The organic solvent may be cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, etc.; chain carbonates such as dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, etc.; ethers such as 1,2-dimethoxyethane, diglyme (diethylene glycol dimethyl ether), triglyme (triethylene glycol dimethyl ether), tetraglyme (tetraethylene glycol dimethyl ether), methoxyethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, etc.; cyclic esters such as γ-butyrolactone, etc.; mononitriles such as acetonitrile, propionitrile, etc.; and one or more of these may be used. In particular, it is preferable to use the carbonate and ether in combination.

[0054] When a carbonate and an ether are used in combination as a non-aqueous electrolyte solvent, the ratio (mixing ratio) of the carbonate to the ether in the total solvent is preferably, by volume, carbonate:ether=30:70 to 70:30.

[0055] The concentration of the electrolyte in the nonaqueous electrolyte is preferably 0.3 to 1.5 mol / l.

[0056] Furthermore, additives may be added to the non-aqueous electrolyte as necessary to improve storage characteristics at high temperatures, etc. Usable additives include saturated sultone compounds such as 1,3-propane sultone and 1,4-butane sultone; unsaturated sultone compounds such as 1,3-propene sultone; acid anhydrides such as maleic anhydride and phthalic anhydride; organic lithium boron salts such as LiB(C2O4)2; dinitriles such as malononitrile, succinonitrile, glutaronitrile, and adiponitrile; and the like, and one or more of these may be used.

[0057] The content of the additive in the non-aqueous electrolyte is, for example, preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and particularly preferably 0.5% by mass or more. On the other hand, if the content of the additive is too high, the internal resistance of the battery may increase and the discharge characteristics may deteriorate, so the content of the additive in the non-aqueous electrolyte is preferably 3% by mass or less, more preferably 2% by mass or less, and particularly preferably 1.5% by mass or less.

[0058] There is no particular limitation on the shape of the non-aqueous electrolyte battery, and various shapes are possible, such as flat (including coin and button), laminate, and tubular (cylindrical and rectangular (rectangular tubular) shapes.) In addition, as the exterior body (battery case) that contains the negative electrode, positive electrode, separator, and non-aqueous electrolyte inside, a combination of a metal can (exterior can) and a lid (sealing can) having an opening, or a metal laminate film can be used.

[0059] Specifically, a flat or cylindrical battery can be produced by crimping an outer can and a sealing can with a gasket between them, or by welding the outer can and the sealing can together to seal them, and a laminated battery can be produced by stacking two sheets of metal laminate film or folding one sheet of metal laminate film and pasting the edges together to seal the battery.

[0060] When using an exterior body that is crimp-sealed, the material of the gasket interposed between the exterior can and the sealed can can be PP, nylon, etc., or, if a high degree of heat resistance is particularly required in relation to the battery's application, heat-resistant resins with a melting point or thermal decomposition temperature of 200°C or higher, such as fluororesins such as PFA, polyphenylene ether (PEE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), PPS, and PEEK, can also be used. Also, if the battery is used in an application that requires heat resistance, a glass hermetic seal can be used for sealing. EXAMPLES

[0061] The present invention will be described in detail below based on examples, but the present invention is not limited to the following examples.

[0062] Example 1 <Preparation of positive electrode> A positive electrode mixture was prepared by mixing manganese dioxide, which is a positive electrode active material, carbon black, which is a conductive additive, and PTFE, which is a binder, in a mass ratio of 90:5:5. The positive electrode mixture was molded to obtain a positive electrode (positive electrode mixture molded body) with a diameter of 16 mm and a thickness of 1.8 mm.

[0063] <Preparation of negative electrode laminate> An aluminum foil having a thickness of 9 μm was pressure-bonded to one side of a lithium foil having a thickness of 1.2 mm, and this was punched out into a circle having a diameter of 16 mm to obtain a laminate of a lithium layer and an aluminum layer.

[0064] Next, acetylene black was dispersed in propylene carbonate to prepare a composition (slurry) for forming a carbon layer, and the slurry was applied onto the aluminum layer of the laminate and dried to prepare a negative electrode laminate in which a carbon layer made of acetylene black was formed on the entire surface of the aluminum layer of the laminate. The basis weight of the carbon layer was 0.5 mg / cm. 2 It was.

[0065] <Preparation of non-aqueous electrolyte> LiClO4 was dissolved at a concentration of 0.5 mol / l in a mixed solvent of propylene carbonate and 1,2-dimethoxyethane in a volume ratio of 1:1, and 2 mass % of 1,3-propane sultone was further added to prepare a non-aqueous electrolyte solution.

[0066] <Battery assembly> Using the above positive electrode and negative electrode laminates and a nonaqueous electrolyte, and using a polymethylpentene nonwoven fabric (thickness: 320 μm) as a separator, a coin-shaped nonaqueous electrolyte primary battery with a diameter of 20 mm and a height of 3.2 mm was assembled in the structure shown in FIG. 1.

[0067] When the negative electrode laminate was brought into contact with the non-aqueous electrolyte, a lithium-aluminum alloy layer was formed on the surface of the lithium layer in the battery, and a negative electrode having a carbon layer further on the lithium-aluminum alloy layer was formed.

[0068] Example 2 The carbon layer on the surface of the negative electrode laminate is set to a weight of 0.02 mg / cm 2 A coin-type non-aqueous electrolyte primary battery was assembled in the same manner as in Example 1, except for the above.

[0069] Example 3 The carbon layer on the surface of the negative electrode laminate is set to a weight of 0.2 mg / cm 2 A coin-type nonaqueous electrolyte primary battery was assembled in the same manner as in Example 1, except for the above.

[0070] Example 4 The carbon layer on the surface of the negative electrode laminate is set to a weight of 1 mg / cm 2 A coin-type nonaqueous electrolyte primary battery was assembled in the same manner as in Example 1, except for the above.

[0071] Example 5 A coin-type non-aqueous electrolyte primary battery was assembled in the same manner as in Example 1, except that a slurry was prepared by dispersing acetylene black in 1,2-dimethoxyethane, and the carbon layer was formed using the slurry.

[0072] Example 6 The carbon layer on the surface of the negative electrode laminate is set to a weight of 0.02 mg / cm 2 A coin-type nonaqueous electrolyte primary battery was assembled in the same manner as in Example 5, except for the above.

[0073] Example 7 The carbon layer on the surface of the negative electrode laminate is set to a weight of 0.2 mg / cm 2 A coin-type nonaqueous electrolyte primary battery was assembled in the same manner as in Example 5, except for the above.

[0074] Example 8 The carbon layer on the surface of the negative electrode laminate is set to a weight of 1 mg / cm 2 A coin-type nonaqueous electrolyte primary battery was assembled in the same manner as in Example 5, except for the above.

[0075] Comparative Example 1 The slurry prepared in Example 1 was applied to one side of a lithium foil having a thickness of 1.2 mm, and then dried to prepare a laminate of a lithium layer and a carbon layer, in which a carbon layer was formed over the entire surface of one side of the lithium layer. The basis weight of the carbon layer was 0.5 mg / cm. 2 A coin-type non-aqueous electrolyte primary battery was assembled in the same manner as in Example 1, except that the laminate was used instead of the negative electrode laminate of Example 1.

[0076] Comparative Example 2 A coin-type nonaqueous electrolyte primary battery was assembled in the same manner as in Comparative Example 1, except that the slurry prepared in Example 5 was used to form the carbon layer.

[0077] Comparative Example 3 A coin-type nonaqueous electrolyte primary battery was assembled in the same manner as in Example 1, except that the carbon layer-forming composition was not applied to the surface of the laminate of the lithium layer and the aluminum layer, and the laminate was used as is to assemble the battery.

[0078] Each of the batteries of Examples 1 to 8 and Comparative Examples 1 to 3 was kept in a thermostatic chamber at -40°C. After the temperature of the battery had dropped, it was discharged at a current value of 10 mA. The discharge voltage (CCV) of the battery 8 ms after the start of discharge was measured to evaluate the load characteristics at low temperatures before storage.

[0079] In addition to the above evaluation, the batteries of Examples 1 to 8 and Comparative Examples 1 to 3 were stored in a high-temperature environment of 120° C. for 500 hours, and then the discharge voltage of the batteries was measured in the same manner as above to evaluate the load characteristics at low temperatures after high-temperature storage. The respective measurement results are shown in Table 1 and FIG. 2.

[0080] [Table 1]

[0081] As shown in the results in FIG. 2, in the batteries of Examples 1 to 4 and the batteries of Examples 5 to 8, in which a lithium-aluminum alloy layer was formed on the surface of the lithium layer of the negative electrode and a carbon layer was further formed on the lithium-aluminum alloy layer, the discharge voltage of the battery increased as the basis weight of the carbon layer increased both before storage and after high-temperature storage, and the load characteristics at low temperatures were improved.

[0082] In addition, the batteries of Examples 5 to 8, which used DME as the solvent for the carbon layer-forming composition, were able to increase the discharge voltage of the battery compared to the batteries of Examples 1 to 4, which used PC, and furthermore, were able to suppress the decrease in discharge voltage due to high-temperature storage. This is believed to be because the carbon layer-forming composition using DME as the solvent had better carbon dispersibility, allowing the formation of a homogeneous carbon layer, and did not cause problems such as the generation of lithium carbonate that occurs when PC is used as the solvent.

[0083] On the other hand, in the batteries of Comparative Examples 1 and 2 in which a carbon layer was formed directly on the surface of the lithium layer, the weight of the carbon layer was 0.5 mg / cm 2 Even when the lithium-aluminum alloy layer was formed on the surface of the lithium layer, the discharge voltage drop due to high-temperature storage was large, about 1 V. Similarly, in the battery of Comparative Example 3 in which a lithium-aluminum alloy layer was formed on the surface of the lithium layer but no carbon layer was formed thereon, the discharge voltage drop due to high-temperature storage was large, about 1 V.

[0084] In the battery of the present invention, as shown in Table 1, by forming a lithium-aluminum alloy layer between the lithium layer and the carbon layer, the decrease in discharge voltage due to high-temperature storage can be sufficiently suppressed even if the basis weight of the carbon layer is reduced.

[0085] The present invention can be implemented in other forms than those described above without departing from the spirit of the present invention. The embodiments disclosed in this application are merely examples, and the present invention is not limited to these embodiments. The scope of the present invention shall be interpreted in accordance with the description of the appended claims rather than the description of the above specification, and all modifications within the scope of the claims are included in the scope of the claims. [Industrial Applicability]

[0086] The nonaqueous electrolyte battery of the present invention is primarily in the form of a primary battery, but can also be in the form of a secondary battery, and can be used in a variety of applications in which conventionally known nonaqueous electrolyte primary batteries and nonaqueous electrolyte secondary batteries are used. [Explanation of symbols]

[0087] 1 Nonaqueous electrolyte battery 2 Positive electrode 3 Negative electrode 4. Separator 5 Outer can 6 Sealed cans 7 Insulation gasket

Claims

1. A non-aqueous electrolyte battery having a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte, the negative electrode has a lithium layer having a lithium-aluminum alloy layer formed on a surface thereof, A carbon layer is further provided on the lithium-aluminum alloy layer, The nonaqueous electrolyte battery according to claim 1, wherein the carbon layer has a basis weight of 0.15 mg / cm 2 or more.

2. The non-aqueous electrolyte battery according to claim 1, wherein the carbon layer has a basis weight of 1.5 mg / cm 2 or less.

3. A non-aqueous electrolyte battery as described in claim 1 or 2, wherein the carbon layer contains carbon black or graphite.

4. A non-aqueous electrolyte battery according to claim 1, wherein the carbon layer contains a binder.

5. A non-aqueous electrolyte battery as described in any of claims 1 to 4, wherein the positive electrode contains, as a positive electrode active material, manganese dioxide or a lithium-containing manganese oxide having the same crystal structure as manganese dioxide and having a Li content of 3.5 mass% or less.

6. The non-aqueous electrolyte battery according to claim 1, wherein the negative electrode has an area ratio of the portion of the surface of the lithium layer where the lithium-aluminum alloy layer is formed being 40% or more.

7. The non-aqueous electrolyte battery according to claim 6, wherein the negative electrode has the lithium-aluminum alloy layer formed on the entire surface of the lithium layer.

8. The non-aqueous electrolyte battery according to claim 1, wherein the negative electrode has an area ratio of the portion on the surface of the lithium-aluminum alloy layer where the carbon layer is formed being 70% or more.

9. The non-aqueous electrolyte battery according to claim 8, wherein the negative electrode has the carbon layer formed on the entire surface of the lithium-aluminum alloy layer.

Citation Information

Patent Citations

  • Negative electrode for lithium battery

    JP1991216960A

  • Lithium battery negative electrode and manufacture thereof

    JP1992162372A

  • Nonaqueous electrolytic solution and nonaqueous electrolyte battery using it

    JP2004047413A

  • Battery

    JP2006269173A

  • Nonaqueous electrolyte battery

    JP2010086736A